2012
DOI: 10.1007/s10067-012-2147-5
|View full text |Cite
|
Sign up to set email alerts
|

The detection of calcium pyrophosphate crystals in sequential synovial fluid examinations of patients with osteoarthritis: once positive, always positive

Abstract: The aim of this study was to investigate whether calcium pyrophosphate dihydrate (CPPD) crystals are constantly detectable in sequential synovial fluid (SF) examinations of patients with initially CPPD-positive osteoarthritis (OA). For this purpose, we searched our SF database for CPPD-positive patients, who had two or more SF analyses between 2008 and 2012 to get sequential information. The database contains SF data determined by a standardised procedure. Of 1,878 samples, examined within the defined time per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Based on the limited available evidence, EDTA preservation for several days seems comparable with instantaneous performed polarized light microscopy [14,16,17]. Thirdly, we used a conventional laboratory centrifuge, in contrast to other studies which used cytocentrifuges [6,7,9,10,[23][24][25][26]. Besides some disadvantages, mentioned before, the latter has important advantages: sedimentable particles from liquid suspensions can be directly transferred as a concentrated thin layer of cells onto a microscope slide without additional manual pipetting and it places cells and crystals in the same optical plane [6,7,9].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Based on the limited available evidence, EDTA preservation for several days seems comparable with instantaneous performed polarized light microscopy [14,16,17]. Thirdly, we used a conventional laboratory centrifuge, in contrast to other studies which used cytocentrifuges [6,7,9,10,[23][24][25][26]. Besides some disadvantages, mentioned before, the latter has important advantages: sedimentable particles from liquid suspensions can be directly transferred as a concentrated thin layer of cells onto a microscope slide without additional manual pipetting and it places cells and crystals in the same optical plane [6,7,9].…”
Section: Discussionmentioning
confidence: 97%
“…We already have shown that all samples that were MSU and CPP positive before centrifugation were also positive after. The centrifugation settings we used were chosen to increase comparability to other studies [6,7,9,10,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
“…Adequate calcium intake is the basis of osteoblast growth. Observation of the dysregulated expression of calcium related gene may partially explain why calcium pyrophosphate dihydrates accumulate in synovial of OA patients [42], [43]. Endocytosis and autophagy are the major pathways for materials to be transported into the lysosomes in cells.…”
Section: Discussionmentioning
confidence: 99%